INTEGRATION OF THE VALUES OF JUSTICE, BENEFIT, ND LEGAL CERTAINTY IN ARRANGEMENT LAND ACQUISITION FOR PUBLIC INTEREST - Silvy Vebritha; Widaningsih (RADJA PUBLIKA, 2025)
Improvement need infrastructure public make procurement land as room sensitive between mandate development and protection right constitutional citizens ; because that , the settings No Enough understood legally -formally, but rather must based on integration mark justice , benefit and certainty law . Research This aim formulate as well as testing the evaluation model operations that ensure third mark present consistent in every stages — planning , preparation , implementation , and delivery results — in framework law positive Indonesia. The method used is enriched juridical -normative approach socio -legal, with the unit of analysis covers material primary law (UUD 1945, UUPA, UU 2/2012, PP 19/2021, and regulations implementer ) and material secondary published ; data analyzed in a way grammatical , systematic , and teleological , then mapped to indicator operational : participation meaning and mechanism objection ( justice ), rationality interest general and efficiency procedural ( benefit ), as well as procedure transparent , documented , and can tested ( certainty law ). The results show framework normative Actually adequate , but there is gap implementation on quality participation , formulation compensation that has not been accommodate non-material losses , and inconsistencies documentation and a resolution forum disputes at the level area . In conclusion , integration most effective value realized as a checklist cross binding stage​ actors , flow , deadlines , and document formats standard ; certainty drafted laws​ Good become prerequisite presence justice substantive and achievable benefits public . Implications practically covering need Operational regulations , digitalization​ system information land For transparency and audit trail , strengthening team coordination cross agencies , as well as supervision participatory for legitimacy social and fluency project public can improved in a way sustainable research​ support the development agenda index integration grades and studies comparative cross area for measuring performance as well as perfect design policy based proof in a way national measurable